2004
DOI: 10.2139/ssrn.539522
|View full text |Cite
|
Sign up to set email alerts
|

Trade Policy and the Household Distribution of Income

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…However, it is conclusive that for liberal countries (Brazil, Peru, Chile, Uruguay) reduction in tariff rate generates increase in economic inequality in the period 1990 -2010 and for moderate countries (Argentina, Bolivia, Colombia, Ecuador, Paraguay) augmentation in tariff rate and trade restriction increases economic inequality in the period 1990 -2010. Findings in this research are coherent with the results of Francois & Rojas-Romagosa who found that in relatively low-income countries high import protection, such as tariffs, is associated with greater inequality, but in relatively high-income countries high levels of protection improve income distribution (Francois & Rojas-Romagosa, 2004).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…However, it is conclusive that for liberal countries (Brazil, Peru, Chile, Uruguay) reduction in tariff rate generates increase in economic inequality in the period 1990 -2010 and for moderate countries (Argentina, Bolivia, Colombia, Ecuador, Paraguay) augmentation in tariff rate and trade restriction increases economic inequality in the period 1990 -2010. Findings in this research are coherent with the results of Francois & Rojas-Romagosa who found that in relatively low-income countries high import protection, such as tariffs, is associated with greater inequality, but in relatively high-income countries high levels of protection improve income distribution (Francois & Rojas-Romagosa, 2004).…”
Section: Discussionsupporting
confidence: 90%
“…Latin America is in an intermediate position (Nissanke & Thorbecke, 2010). However, studies about inequality found that income distribution tends to be worse for countries with labour-intensive diversification than those that apply import substitution policies (Francois & Rojas-Romagosa, 2004). civilizar 11 Ángela Isabel Giraldo Suárez For the region, an analysis of income inequality in three Latin American countries, Argentina, Brazil and Mexico during the period 2000-2010, evidenced that inequality has declined significantly (Lustig, Lopez-Calva, Ortiz-Juarez, & Cases, 2012) the Gini coefficient declined in 13 of 17 Latin American countries.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations